Strengthening Human Resource Capacity through Digital Marketing Mentoring: Waste Bank Empowerment for Circular Economy Sustainability - Ratnawati, Shinta; Mujib, Miftachul; Alfath Nurul Fathony, Ikhwan; Marva Ondrea Sugiyarto, Jauzaa; Subur Santoso, Rahmat (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2026)
Background: Gunungpring Village in Magelang District faces serious waste management challenges despite its strategic position as a religious and educational tourism center. This community service program was designed to enhance the digital marketing skills of waste bank administrators, thereby increasing the economic value of recycled products and supporting the sustainability of the circular economy. Purpose of the Study: This program aimed to enhance participants’ abilities in product design, pricing strategies, and the implementation of digital marketing through e-commerce and social media platforms. Method: The mentoring activities were conducted over six months using a participatory approach involving 40 participants and four mentors. The program included training sessions, workshops, hands-on digital marketing practice, and monitoring through pre–post tests, sales analysis, and participant reflection. Result: the program resulted in a 21-point increase in participants’ knowledge scores and an average 10% increase in monthly product sales. Beyond these measurable outcomes, the mentoring activities improved participants’ digital confidence, collaboration, and motivation. These findings demonstrate that strengthening human resource capacity through digital marketing mentoring can effectively support community economic empowerment and enhance the sustainability of circular economy–based waste management initiatives.